Analysis of knowledge-based economy impact on economic development in the European Union countries - Dworak, Edyta (Comparative Economic Research. Central and Eastern Europe, 2011)
Directions of changes in the world economy occurring in recent years show the transition from industrial era economy to knowledge-based economy. Increasing investments in fixed assets is no longer a sufficient way of ensuring permanent economic growth. Research-development activity, innovation and human capital become decisive factors of development. As an essential determinant of the innovativeness level of individual economies are considered expenditures on research and development designed to conduct basic, applied research and development activities as well as effects of these research appearing in the form of innovations. The objective of the article is to analyze correlative connections between the two main variables describing knowledge-based economy, that is between the share of R&D expenditures in GDP and R&D expenditures per capita, and the remaining characteristics of knowledge - based economy. Another aim of the article is to assess the impact of these two variables on the basic macroeconomic indicators in the European Union countries, and, connected with them, to analyze the impact of knowledge-based economy on economic development of these countries.